Impacts of unconventional oil and gas development on atmospheric aerosol particles - Evanoski-Cole, Ashley R., author; Collett, Jeffrey L., advisor; Kreidenweis, Sonia M., committee member; Pierce, Jeffrey R., committee member; Ham, Jay, committee member (Colorado State University. Libraries, 2017)
Rising demands for global energy production and shifts in the economics of fossil fuel production have recently driven rapid increases in unconventional oil and gas drilling operations in the United States. Limited field measurements of atmospheric aerosol particles have been conducted to understand the impacts of unconventional oil and gas extraction on air quality. These impacts can include emissions of greenhouse gases, the release of volatile organic compounds that can be hazardous and precursors to tropospheric ozone formation, and increases in atmospheric aerosol particles. Aerosol particles can also contribute to climate change, degrade visibility and negatively impact human health and the environment. Aerosol formation can result from a variety of activities associated with oil and gas drilling operations, including emission of particles and/or particle precursors such as nitrogen oxides from on-site power generation, evaporation or leaking of fracking fluids or the produced fuel, flaring, the generation of road dust, and increases in traffic and other anthropogenic emissions associated with growing populations near drilling locations. The work presented here details how activities associated with unconventional oil and gas extraction impact aerosol particle characteristics, sources, and formation in remote regions. An air quality field study was conducted in the Bakken formation region during a period of rapid growth in oil production by unconventional techniques over two winters in 2013 and 2014. The location and time of year were chosen because long term IMPROVE network monitoring records show an increasing trend in particulate nitrate concentrations and haze in the Bakken region during the winter, strongly contrasting with sharp decreases observed across most of the U.S. The comprehensive suite of instrumentation deployed for the Bakken Air Quality Study (BAQS) included measurements of aerosol concentrations, composition, and scattering, gaseous precursors important for aerosol formation, volatile organic compounds, and meteorology. Regional measurements of inorganic aerosol composition were collected, with average concentrations of total inorganic PM2.5 between 4.78 – 6.77 µg m-3 and 1.99 – 2.52 µg m-3 for all sampling sites during the 2013 and 2014 study periods, respectively. The maximum inorganic PM2.5 concentration observed was 21.3 µg m-3 for a 48 hour filter sample collected at Fort Union National Historical Site, a site located within a dense area of oil wells. Organic aerosol measurements obtained during the second study at the north unit of Theodore Roosevelt National Park (THRO-N) featured an average concentration of 1.1 ± 0.7 µg m-3. While oil production increased from 2013 to 2014, the lower PM2.5 in 2014 can be explained by the meteorological differences. During the first study, increased snow cover, atmospheric stability, solar illumination, and differences in the dominant wind direction contributed to higher PM2.5. The enhanced concentrations of inorganic PM2.5 measured in the Bakken region were tied to regional oil and gas development. Elevated concentrations of PM2.5 were observed during periods of air mass stagnation and recirculation and were associated with VOC emissions aged less than a day, both indicating a predominant influence from local emissions. High PM2.5 concentrations occurred when low i-/n-pentane VOC ratios were observed, indicating strong contributions from oil and gas operations. The hourly measurements of gas and aerosol species in an extremely cold environment also provided a unique data set to investigate how well thermodynamic aerosol models represent the partitioning of ammonium nitrate. In general, during the coldest temperatures, the models overpredicted the formation of particulate nitrate. The formation of additional PM2.5 in this region is more sensitive to availability of N(-III) species during the coldest periods but increasingly sensitive to available N(V) when temperatures are relatively warmer and ammonia availability increases. These measurements and modeling results show that continued growth of oil and gas drilling operations in remote areas such as the Bakken region could lead to increased PM2.5 and impact haze formation in nearby federally protected lands.
Keywords: air quality; haze; aerosol; oil and gas; Bakken